PROTOTIPE SAJADAH OTOMATIS ARAH KIBLAT DENGAN MIKROKONTROLER ARDUINO - Abdul Rafid Fakhrun Gani; Yul Ifda Tanjung; Abdul Rasyid Fakhrun Gani; Aji Ibnu Khair; Muhammad Jaka Maulana; Ilham Sidiq (Universitas Negeri Medan, 2022)
Prayer is an obligation for Muslims in the context of worship, which means that a Muslim is obliged to pray even though he is in a vehicle. In carrying out prayers, there are several conditions for valid prayer, including facing the Qibla direction, scholars argue that facing the Qibla direction is a valid condition for prayer. However, when a Muslim prays in a vehicle, the relative qibla direction of the place changes as the vehicle turns direction. With the aim of making it easier for Muslims to carry out prayers in a vehicle